Peran Modal Intelektual dalam Memoderasi Pengaruh Ambideksteritas Keuangan Terhadap Nilai Perusahaan LQ 45 - Rusfian, Rusfian; Widhiastuti, Susanti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study explores the influence of intellectual capital as a moderator of the connection among financial ambidexterity and corporate value. The study focuses on corporates that have consistently been included in the LQ45 list on the Indonesia Stock Exchange (IDX) during the study period of year 2018 to 2023. A purposive sampling method was applied to choose 25 companies for the study. The study relies on secondary data gathered from the companies’ financial statement found on the IDX website.The analysis was performed using the SEM-PLS method with Warp-PLS 8.0 software, achieving a conviction level of 95%. The results reveal that intellectual capital serve as a moderating factor in the influence of financial ambidexterity, measured by asset growth, on corporate value. However, it does not act as a moderator for financial ambidexterity measured by sales growth and profit growth in relation to corporate value. Additionally, financial ambidexterity as measured by asset growth, is proven to affect corporate value, while it does not significantly influence corporate value when assessed through sales growth and profit growth.